Kontribusi Istri Nelayan Terhadap Pendapatan Keluarga Pada “Musim Baratan” - Candrakuncaraningsih, Venomena (Universitas Islam Negeri Sunan Kudus, 2020)
The moment’s in order to help her husband’s work to meet family need’s, a fishermen’s wife has a multiple roles in the family, namely as housewife and also as breadwinner. It was done especially in the western seasons, because at this time the husband’s income is greatly reduced compared to normal days. The purpose of this paper is to examine how much the fishermen’s wife’s contribution to family income in the western season from an islamic perspective in The District of Kragan in Rembang Regency. As for the data used in this study are primary data and secondary data. The variable used is the income of fishermen and fishermens wifes in the wester seasons (Desember 2019 and January 2020). Determination of the method used is “Simple Random Sampling” with the data collected analyzed with “Multiple Linear Regression” models for the income of fishermen’s wifes, then the result are compared with the income of the fishermens. The result of the study showed that the contribution of the fishermen’s wifes was very large in the western season, compared to husband’s income that is equal 68 %. This contribution is said to be high because > 30%. Age, education, number of dependents of famlily and work simultaneously do not significantly affect to income. And partialy also does not affect the income of fishermen’s wives. So this is very helpfull in meeting family needs when the situation occurs. Women in islamic perspective have an important role in the economy, they are given the rights to own wealth. Islam allow women to work, because work is worship. As long as they do neglect their responsibilities in managing household.